Design and Characterization of Nystatin Solid Dispersion for Improved Treatment of Fungal Infections (International Journal of Food and Nutritional Sciences, 2022)
The objective of present research work was to develop solid dispersion of Nystatin by usingdifferent concentrations of drug and polymer ratio. The effect of different concentrations ofpolymers was determined on the drug content and percentage cumulative drug release. Drugrelease followed zero-order models and mechanism of drug release are independent on theconcentration of a drug.